The potential role of Pegadaian in supporting MSMEs: Perspectives from MSMEs entrepreneurs - Ni Nyoman Padang Cakra Binaraesa; Ikayanti; Nuryadi (Journal of Economic, Business & Accounting Research, 2026)
Background: Micro, small, and medium enterprises (MSME) constitute the backbone of Indonesia’s people-centered economy; however, limited access to formal financing remains a significant structural constraint on their business sustainability. Existing literature on the role of Pegadaian (the Indonesian state-owned pawnshop institution) is predominantly characterized by quantitative and institutional approaches, leaving the subjective perspectives and lived experiences of MSME actors, the primary agents of the people’s economy largely underexplored. Methods: This study adopts a qualitative approach using a single case study design to obtain an in-depth understanding within a real-life context. Data were collected through in-depth interviews with a micro-entrepreneur operating a canteen business in Surabaya and analyzed using thematic analysis to identify patterns and meanings related to financing dynamics and institutional perceptions. Findings: The findings indicate that MSME actors tend to rely on self-financing to minimize financial risk and avoid social stigma associated with debt. A major operational challenge identified is seasonal income fluctuation, which threatens daily cash flow stability. Although Pegadaian is perceived as highly accessible with fast procedures, its utilization is constrained by low financial literacy and fears related to interest burdens and collection risks. Nevertheless, a form of latent trust emerges, as the informant acknowledges Pegadaian’s substantial potential as a liquidity provider for fellow MSME actors. Conclusion: Pegadaian holds strategic potential as a financial buffer that is crucial for MSME resilience in coping with short-term economic shocks. The success of financial inclusion depends not only on physical access to financial services but also on strengthening financial literacy and building trust through empathetic communication. Novelty/Originality of this article: The originality of this study lies in addressing an academic gap by presenting a qualitative perspective that highlights the psychosocial and cognitive dimensions of micro-entrepreneurs, offering a more contextualized and nuanced understanding of financial inclusion barriers that have been overlooked in conventional studies.